COMPARATIVE STUDY OF MINERAL CONTENT OF SIDAT FISH MEAT (ANGUILLA MARMORATA QUOY GAIMARD) ON YELLOW EEL PHASE FROM PALU RIVER AND LAKE POSO - Jamaluddin Jamaluddin; Widodo Agustinus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Eel fish (Anguilla marmorata Quoy Gaimard) is one of the strategic commodities to be developed because it has high nutritional value such as protein, fatty acid, vitamins and minerals. Minerals are one of the nutrients the body needs for the body's physiological processes. This study aims to determine the amount and mineral content of eel meat Anguilla marmorata Quoy Gaimard) originating from the river Palu and lake Poso. Sampling was done by Purposive sampling method based on type, weight 35-40 gram, size 300-450 mm and location of taking. Mineral testing on eel meat using laboratory experimental with Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The results showed that the mineral content contained in yellow eel fish from Palu river contains potassium 1,519 mg/kg, magnesium 203 mg/kg, zinc 11,2 mg/kg, and mercury 0,129 mg/kg; and from the Poso lake contains potassium 1,360 mg/kg, magnesium 179 mg/kg, and strontium 1.32 mg/kg. Based on this study can be concluded that there is influence the location against the amount of mineral content.